HUBUNGAN PEMBERIAN STIMULASI DENGAN PERKEMBANGAN BALITA USIA 1-5 TAHUN DI POSYANDU SERUNAI VII KELURAHAN VI SUKU WILAYAH KERJA PUSKESMAS TANAH GARAM KOTA SOLOK - Afridon Afridon (Ensiklopedia Education Review, 2019)
Factors affecting growth and development are genetic, environmental (prenatal, and post natal), post-natal environments that affect children's growth and development in general can be classified as biological environments. One factor that influences development is stimulation. The type of research used is descriptive analytic with Cross Sectional Study design in which to see the relationship between two variables. The variable in this study is the independent variable is the provision of stimulation and the dependent variable is the development of toddlers aged 1-5 years. Based on the results of research conducted on 34 respondents, it is known that more than a portion (64.7%) of respondents provide developmental stimulation in infants, more than a portion (61.8%) of infants of respondents have appropriate development and analysis results between the provision of stimulation and development under-five children were found to be more than a part (66.7%) who did not provide stimulation that experienced dubious development. While statistically obtained p value = 0.025 ˂ 0.05, which means that there is a significant relationship between those who do not provide stimulation with the development of children who have doubts. It is expected that health workers provide information on how to provide stimulus to their toddlers in accordance with the stage of development of their age so that respondents are able to provide stimulus to their children.